Techno-economic assessment of 5G infrastructure sharing business models in rural areas - Koratagere Anantha Kumar, Shruthi; Oughton, Edward J. (Frontiers in Computer Science, 2023)
How cost-efficient are potential infrastructure sharing business models for the 5G era (and beyond)? This significant question needs to be addressed if we are to deliver universal affordable broadband in line with Target 9.1 of the UN Sustainable Development Goals. Although almost twothirds of the global population is now connected, many users still lack access to high-speed and reliable broadband connectivity. Indeed, some of the largest connectivity issues are associated with those living in areas of low economic viability. Consequently, this assessment evaluates the cost implications of different infrastructure sharing business models. The results indicate that a rural 5G neutral host network (NHN) strategy helps to reduce total cost between 10-50% compared with other sharing strategies. We also find that, compared to a baseline strategy withNo Sharing, the net present value of rural 5G sharing strategies can earn between 30-90% more profit. The network upgrades to 5G using various sharing strategies are most sensitive to changes in the average revenue per user, the adoption rate, and the amount of existing site infrastructure. For example, the results from this study show that a 20% variation in demand revenue is estimated to increase the net present value of the sharing strategies by 2-5 times compared to the No Sharing strategy. Similarly, a 10% increase in existing infrastructure lowers the net present value by 8-30%.